The 3-Item "Apathy" Subscale Within the GDS-15 Is Not Supported in De Novo Parkinson's Disease Patients: Analysis of the PPMI Cohort. (May 2022) - Szymkowicz, Sarah M.; Ellis, Liam J.; May, Pamela E.
This study examined individual components of the Geriatric Depression Scale-15 (GDS-15) to determine whether the 3-item Withdrawal-Apathy-Lack of Vigor (WAV) subscale, which has been validated in older adults and advanced Parkinson's disease (PD), was applicable to newly diagnosed patients with PD. Baseline Parkinson's Progression Markers Initiative (PPMI) data (n = 345), including GDS-15 and Movement Disorder Society—Unified Parkinson's Disease Rating Scale (MDS-UPDRS) depression, apathy, and anxiety scores, were examined. Data reduction techniques (i.e., principal components, confirmatory factor analyses) were used. Model fit was poor for the previously identified GDS-15 factor structures. Via principal components analysis, 5 components were identified, none of which reflected the 3-item WAV subscale previously reported in the literature. Internal consistency of the GDS-15 was acceptable, as was the internal consistency for the largest component (labeled "Dysphoria"). All 5 components significantly correlated with the MDS-UPDRS depression, apathy, and anxiety items. Model fit was fair for the "Dysphoria" factor only. Overall, the 3-item WAV factor reported in previous literature was not supported in this sample of de novo PD patients.